Paradojas del familiarismo en el Estado del bienestar: mujeres y renta básica - Añón, María José; Miravet, Pablo (Cuadernos de Relaciones Laborales, 2006)
In this study we try to show how the special feature of mediterranean family is related with public policies and law in southern Europe Welfare States. In the present conditions of structural changes, this characteristic relationship has outstanding consequences for women in public sphere but also in the private life. As far as public policies continue holding on family solidarity, they are ineffective to remove the subordinate rol of women. In this framework, we intend to give some reasons why an unconditional income guarantee is an appropriate policy to bring face that subordinate rol.
Keywords: «familism»; «familialism»; subordination; basic income